Drought analysis using copula approach: a case study for Turkey. Issue 3 (3rd July 2019) - Evkaya, Ozan; igil, Ceylan Yozgatl; Sevtap Selcuk-Kestel, A.
Abstract: Drought is one of the most drastic natural phenomenon, having devastating economic and environmental damages. Most studies related to drought monitoring consider quantitative indices, primarily based on univariate drought indicator. Besides, drought characteristics are important to monitor the impacts of drought on any specific area. The objective of this study is to introduce a new drought index using copula approach. Additionally, drought duration, severity and peak intensity are analyzed based on various drought indices. The dependence among characteristics are exploited and return period calculations are compared. For that purpose, monthly meteorological data for Aksehir Station in Konya are investigated.